Women's participation and support for the implementation of the closed fishing season in Davao Gulf, Philippines. (September 2022) - Macusi, Edison D.; Macusi, Erna S.; Canales, Charlen Mae G.; Barboza, Anna; Digal, Larry N.
Abstract: Women living in coastal areas around the Davao Gulf mainly participate as gleaners, fishers, traders, fish farmers, and fish processors in the small-scale fisheries (SSF). However, there is little information about their participation in the management of their fisheries resources. They remain invisible considering their contributions to policy implementations, including during the closed fishing season. Thus, this study aimed to describe the roles of women, their access to community services, and their support for the implementation of the closed fishing season in Davao Gulf, Philippines. Survey data on women respondents (N = 255) were collected in six sites, collecting information on their involvement in fishing and fishery-related activities. The information was validated through seven focus groups (N = 112). Results showed that respondents live near the shore, poorly educated or attended elementary level, and are members of fishing families. They engaged in gleaning and have access to loans through microfinance institutions to address food security concerns, their children's education, and other household needs. Women also strongly supported the implementation of the closed fishing season, mainly through awareness and education campaigns during meetings. However, most of the respondents failed to connect to fishing organizations as these were male-dominated, and very few community organizations engaged women. Hence, women were underrepresented, and their opinions were undervalued in the management programs in Davao Gulf. To improve the situation, future training and livelihood programs in the fisheries should actively engage women and make all efforts to be more inclusive in community programs or projects.